2014
DOI: 10.1089/lap.2013.0158
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Vaginoplasty Using a Sigmoid Graft Through the Umbilical Single-Incision Hybrid Transperineal Approach: Our Initial Experience

Abstract: Transumbilical single-incision hybrid transperineal laparoscopic sigmoid vaginoplasty offers a feasible scarless approach for females with MRKH syndrome. The favorable cosmetic results would favor use of this type of vaginoplasty as an alternative to the conventional laparoscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Previous reports of LSV showed that to retract the descending colon either enlargement of the port incision, minilaparatomy, including gasless laparoscopy, or one port technique be performed [3,[11][12][13]. Abdominal wall incisions are associated with a risk of infection, herniation, pain and scarring [3,4]. Since vaginoplasty requires creation of a perineal tunnel we used it to retract the descending colon and avoid an unnecessary additional incision to the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports of LSV showed that to retract the descending colon either enlargement of the port incision, minilaparatomy, including gasless laparoscopy, or one port technique be performed [3,[11][12][13]. Abdominal wall incisions are associated with a risk of infection, herniation, pain and scarring [3,4]. Since vaginoplasty requires creation of a perineal tunnel we used it to retract the descending colon and avoid an unnecessary additional incision to the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…One of the disadvantages of LSV is enlargement of the portal incision or minilaparotomy performed to retract the descending colon through the abdominal wall for the suture of an anvil of the circular stapler before restoration of the continuity of the intestinal tract. Abdominal wall incisions are associated with a risk of infection, herniation, pain and scar formation [3,4]. To avoid this, we describe a novel perineal approach technique.…”
Section: Introductionmentioning
confidence: 99%
“…Ostrzenski established a classification for a wide vagina from category A to D based on the presence/absence of columnar rugae and site-specific defects [6] ( Table 3). Vaginoplasty is mostly performed for patients with congenital vaginal deformities, women with a dysfunctional vagina, women with disorders of sex development, male-to-female transgender women in the medical literature [7][8][9][10][11][12][13], peritoneal vaginoplasty, intestinal vaginoplasty, and vaginoplasty with autologous buccal micromucosa [14][15][16][17][18][19]. In our case series, we include patients without any noticeable congenital deformity who seek improved sexual function and they do not require such an invasive surgical treatment for the correction of their vagina.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of creating neovagina is to create a canal with an appropriate length, diameter, and axis and normal lubrication for a desirable sexual intercourse [7,8]. Using rectosigmoid to make neovagina is among the new methods of creating neovagina [9][10][11].…”
Section: Introductionmentioning
confidence: 99%